Topoisomerase activity assays in Neurospora - A. L. Schroeder; M. F. Lavin; S. Bohnet (Fungal Genetics Reports, 1989)
DNA topoisomerases are enzymes capable of altering the topological conformation of DNA by inducing transient single (Topoisomerase I) and double strand (Topoisomerase II) breaks.